Improving the bread quality and endophytic yeast of Salak Pondoh (Salacca edulis Reinw.) growth by addition of phosphate source - Yuanita Refa Kusuma; Ulfah Utami; Nur Kusmiyati (Biogenesis: Jurnal Ilmiah Biologi, 2022)
.